Research Advances and Perspectives on Early Flowering Traits in Cucumber - Meidi Zhang; Ming Ma; Hong Lang; Mingliang Jiang (Plants)
Early flowering refers to the phenomenon in which the first flower appears in fewer days than normal, regardless of the sex of the flower. It is a significant feature impacting the early maturity and economic yield of cucumbers. The early flowering trait of cucumber is influenced by several factors. Considering its heritability, technologies such as whole-genome sequencing, genetic modification, bioinformatics analysis, quantitative trait locus (QTL) mapping, molecular marker-assisted selection, and gene editing are widely used to explore the regulatory genes and molecular mechanisms of the early flowering trait in cucumbers. This review aimed to summarize the factors, QTL mapping, molecular regulation mechanisms, and omics analysis related to early flowering traits in cucumbers. This review contributes theoretical insights to support both cucumber breeding for early flowering and fundamental research on early flowering traits.